On Distant Service : The Life of the First U.S. Foreign Service Officer to Be Assassinated - Stein, Susan M. (Susan Margaret), 1942- (Book collections on Project MUSE., 2020)
"Robert Whitney Imbrie (April 23, 1883-July 18, 1924) was the first U.S. foreign service officer to be murdered for political reasons. This book recounts his life and death"--